Determinação da resistência à flexão de ligas odontológicas, utilizadas em prótese parcial fixa e prótese sobre implante, soldadas por brasagem e a laser - Dinato, José Cícero [UNESP] (1999)
The mechanic properties of brazed joints compared with castings performed in monoblocks have been exhaustingly evaluated. The use of laser in Dentistry opened a new and promising field to study this type of fusion. The purpose of this study was to determine the flexural resistance of four types of metal alloys used in fixed partial prosthodontics (Co-span 13.5, Stabilor G, Deva 4 and Palliag M). Fifteen test specimens with 3 mm diameter and 25mm length were obtained by casting for each alloy, and divided in three groups (monoblocks, brazing and laser welding), totaling sixty cylindrical specimens. The specimens were submitted to GLP/O2 torch welding and Nd-YAG laser welding performed with a specific laser equipment (Laser 2002, Dentaurum, Germany). The results were compared with tests performed in monoblocks of these same materials. To determine the flexural resistance, an universal testing machine (Instrom, model 4301), with a 500 Kg maximum capacity was used. The results were statistically analyzed using an ANOVA and Tuckey'.s test in a 5% degree of probability. The results showed that the highest numeric value of flexural resistance was found with the Co-Span alloy, followed by Deva 4, for both laser welding and monoblock groups. Palliag M showed statistically similar values for the laser welding, brazing and monoblock groups, whereas Stabilor G presented its highest values in brazing